Ordinances of the City of Chicago, Ill., ch. 16, § 1 - (:unkn) unknown (General Publisher, 1851)
Prohibiting the keeping, sale, or giving away of gun powder or gun cotton “in any quantity” absent written permission of the authorities. Punishable by a fine of $25 per offense.
--
Keywords: TRANSFER; MANUFACTURE & STORAGE OF GUNPOWDER